Withdrawal resistance of self-tapping screws inserted on the narrow face of cross laminated timber made from Radiata Pine. (June 2021) - Li, Xin; Ashraf, Mahmud; Subhani, Mahbube; Ghabraie, Kazem; Li, Haitao; Kremer, Paul
Abstract: With the growing global tendency towards sustainable construction techniques, the use of renewable material regains attention from the industry. Cross laminated timber (CLT), as a relatively new engineered timber product, is recognized as a viable alternative to some traditional materials for various of structures. Based on the source of original raw materials, structural responses of CLTs could vary significantly between species. In Australia, locally planted Radiata Pine (Pinus radiata D. Don) is used to manufacture CLT panels by XLam. For panel-to-panel connection in CLT buildings, self-tapping screws (STS) are most used and are typically recommended by CLT producers as a result of their superb resistances and easy installation process. In the current study, Rothoblaas VGS11 STSs were used to investigate their pull-out responses from three-layer CLT panels with overall thickness of 105 mm and 135 mm. STSs were inserted on the narrow face of the considered XLam CLT panels both parallel to the grain direction and perpendicular to the grain direction. Different penetration depth or embedment length were considered to observe the effect of bond area on the bond strength of the STS-to-CLT interface. Typical failure modes and load vs slip curves were recorded during experiment, and were compared with available design rules for predicting withdrawal resistances. It was observed that the theoretical models are quite conservative in terms of predicting withdrawal capacity and strength. The available theoretical models yield an error of up to 57% and 43% when calculating withdrawal resistance and strength, respectively.